The Relationship between Postpartum Mother's Knowledge about Breast Milk Dam and Interest of Breastfeeding Mothers in the Working Area of Eromoko II Health Center - Amita, Migita Vidia; Yunanto, Enyk; Annisa, Nurul (International Journal of Health Science and Technology, 2023)
Background: Mother's knowledge of breast milk has a role in the success or failure of a mother in breastfeeding her baby. The greater the knowledge possessed, the greater the ability to survive in breastfeeding. One of the problems that causes the failure of breastfeeding is due to the presence of breast milk dams. Objective: To determine the relationship between postpartum mothers' knowledge about breast milk dams with the interest of nursing mothers. Method: This type of research is quantitative using a cross sectional study approach. Sampling in this study will use total sampling. The analysis to be used is the Pearson Product Moment, which is a significance value (Sig.) > 0.05. Results: A total of 15 postpartum mothers were respondents in this study. The characteristics of the majority respondents in the age category are not at risk, high school education and working mothers. The frequency distribution of postpartum mothers' knowledge about breast milk dams is mostly in the less category, while the interest of breastfeeding mothers is the majority in the category of not interested in breastfeeding. The data normality test using Shapiro Wilk shows normally distributed data. Then  the Pearson Product Moment test was carried out, namely the significance value (Sig.) > 0.05 so that the conclusion was that there was a relationship between postpartum mothers' knowledge about breast milk dams with the interest of breastfeeding mothers in the work area of the Eromoko II Health Center. Conclusion: The results showed that there was a relationship between postpartum mothers' knowledge about breast milk dams with the interest of breastfeeding mothers in the working area of the Eromoko II Health Center